Analisis Keuntungan dan Nilai Tambah Kakao Pasta di Unit Pengolah Hasil (UPH) Sari Bumi, Desa Gumbrih, Kecamatan Pekutatan, Kabupaten Jembrana - DEWI, NI LUH PRIMA KEMALA; ASTAMA, I KADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Analysis of Benefits and Added Value of Cocoa Pasta in the Sari Bumi Processing Unit (UPH), Gumbrih Village, Pekutatan District, Jembrana Regency The Sari Bumi Processing Unit (UPH), Gumbrih Village, Pekutatan District, Jembrana Regency is the only group that is actively processing fermented cocoa beans into secondary products in Bali Province. There are several types of products processed by the group, one of which is cocoa pasta. Cocoa Pasta is cocoa that is more in demand by consumers, especially for export because this cocoa pasta can be made as an ingredient for making cakes, ice cream and others. Quantitative data used in this study is the cost of raw materials, labor, other inputs, the amount of cocoa pasta production in one production process. The qualitative data used is the processing of Cocoa from Fermented Cocoa Beans into Pasta. Data collection methods used are observation and survey. Determination of the sample of this study was determined by the purposive method, namely the selection of samples deliberately appointed by the Head of UPH. The appointment is based on the duties and responsibilities of UPH Sari Bumi and is considered capable of providing information in accordance with the research objectives. The respondents consisted of three people who were divided into the chairperson, treasurer, and cocoa processing staff. Data analysis using by the Hayami method. The profit obtained by the processor in one production process after deducting the value of labor benefits is a profit of IDR 43,259.75. The added value of cocoa pasta is IDR 50,166.00, meaning that with the addition of secondary products, it will get additional selling value. In one kilogram of pasta, the added value is Rp. 50,166.00.